2002
DOI: 10.1080/00015458.2002.11679269
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Increased Intraabdominal Pressure in Severe Acute Pancreatitis

Abstract: The aim of the study was to assess whether increased intra-abdominal pressure affects the clinical course and reflects on the effectiveness of the conservative treatment in patients with severe acute pancreatitis. Data on 37 consecutive patients with severe acute pancreatitis that were collected prospectively included APACHE II score, daily measurement of the intra-abdominal pressure, and clinical routine. Group A consisted of 26 patients with intra-abdominal pressure < 25 cm/H2O during their treatment period,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 22 publications
3
54
0
1
Order By: Relevance
“…Over the past decade, most studies depicted ACS as a terminal prognostic event, with a reported incidence of IAH and ACS in severe disease of 59% to 84% and 25% to 56% respectively [15][16][17][18][19][20][21]. Wide variability within the literature has resulted from small study population sizes, heterogeneous diagnostic criteria, as well as inconsistent methodology for IAP measurement.…”
Section: Acute Pancreatitismentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past decade, most studies depicted ACS as a terminal prognostic event, with a reported incidence of IAH and ACS in severe disease of 59% to 84% and 25% to 56% respectively [15][16][17][18][19][20][21]. Wide variability within the literature has resulted from small study population sizes, heterogeneous diagnostic criteria, as well as inconsistent methodology for IAP measurement.…”
Section: Acute Pancreatitismentioning
confidence: 99%
“…ACS has been clearly associated with worse outcomes in acute pancreatitis [15]. Over the past decade, most studies depicted ACS as a terminal prognostic event, with a reported incidence of IAH and ACS in severe disease of 59% to 84% and 25% to 56% respectively [15][16][17][18][19][20][21].…”
Section: Acute Pancreatitismentioning
confidence: 99%
See 1 more Smart Citation
“…4 Incidence, Risk Factors, and Indications for IAP Monitoring IAH and ACS occur in a wide variety of patients, including infants, children, and adults who require medical or surgical treatment or treatment for burns, and is associated with a variety of diagnoses. 7,[9][10][11][12] The reported incidence of ACS varies from less than 1% to 60%, depending on the definitions used and the different populations of patients studied. 7,8,[12][13][14] Many health care providers think ACS may be underrecognized and thus underreported.…”
Section: Abdominal Compartment Syndrome In Childrenmentioning
confidence: 99%
“…Finally, intracranial pressure may also be increased due to the decrease in cerebral venous return and increased venous pressure. 4 Increased recognition of its prevalence among the critically ill, combined with advances in both the diagnosis and management of intraabdominal hypertension (IAH) and abdominal compartment syndrome (ACS), have resulted in significant improvements in patient survival. 5,6 Current methodology for intra-abdominal pressure assessment relies on the measurement of bladder pressure.…”
Section: Introductionmentioning
confidence: 99%